Impact of Climate Change on Grain Yield and Variability in Nigeria: A Stochastic Production Model Approach - Aye, G. C.; Ater, P.I. (Richtmann Publishing, 2012)
This paper analyses the impact of climate change on Nigeria’s cereal grain yields, variance and covariance.Maize and rice were selected based on their distinct production in almost all the States in Nigeria. A paneldata stochastic production model with heteroscedasticity was employed in analysing the data. The dataconsists of a panel of eight States and 18 time periods. The eight states spans across the six geopoliticalzones. The cereal grains considered are rice and maize. The simulation results show that there would be anincrease in rice yield whereas its variance would increase. The contrary holds for maize. The covariance ofthe two crops would reduce in future due to climate change. The results have implications for allocations ofagricultural land among crops, for crop production mix, and for adaptation and mitigation policies.